The Recovery of State Losses through Corruption Asset Confiscation: Policies and Obstacles - Syahiruddin Latif; Rizki Ramadani (Indonesian Association for Public Administration (IAPA), 2022)
The success of eradicating corruption is measured not only by the success rate of convicting perpetrators, but also by the rate of recovering state losses. The purpose of this article is to explain the government's legal policies regarding the recovery of state losses through the confiscation of corruption assets, as well as the various obstacles to its implementation. This normative/doctrinal study analyzes secondary data in the form of legal materials using conceptual and statutory approaches. A qualitative-prescriptive narrative is used to present the analysis. In general, the Indonesian government has issued a number of regulations that can be used to recover state losses caused by corruption. This is asserted, among other things, in the Criminal Code, the UNCAC, which the Indonesian government has ratified, and Corruption Laws, which stated that the recovery of state losses can be accomplished through both criminal and civil law procedures. However, the existing policies still face some obstacles, both in terms of unclear legal substance, the ability and commitment of law enforcement officials, to the limitations of facilities and infrastructure.